Gold(I) complexes with chloro(diaryl)silyl ligand. Stoichiometric reactions and catalysis for O-functionalization of organosilane. Issue 15 (10th April 2020) - Tsuchido, Yoshitaka; Kanda, Atsushi; Osakada, Kohtaro
Abstract: An Au(I) complex with a chloro(diphenyl)silyl ligand [Au(SiPh2 Cl)(PCy3 )] (1a ) is obtained from the reaction of Ph2 SiH2 with [AuCl(PCy3 )]. (4-FC6 H4 )2 SiH2, (4-MeC6 H4 )2 SiH2, and Ph2 GeH2 react with [AuCl(PCy3 )] to form complexes with the chlorodiarylsilyl ligand, [Au(SiAr2 Cl)(PCy3 )] (1b : Ar = C6 H4 -4-F, 1c : Ar = C6 H4 -4-Me) and with the chloro(diphenyl)germyl ligand, [Au(GePh2 Cl)(PCy3 )] (2a ), respectively. Complex 1a reacts with H2 O to form Ph2 SiH(OH) and (Ph2 SiH)2 O, whereas the reaction of EtOH with 1a yields Ph2 SiH(OEt) exclusively. Complex 1a catalyzes the hydrolysis of Ph2 SiH2 ([Au]:[H2 SiPh2 ]:[H2 O] = 0.05:1.0:10.0) at 60 °C to yield Ph2 SiH(OH) and (Ph2 SiH)2 O. The reaction of Ph2 SiH2 with HOEt in the presence of a catalytic amount of 1a affords Ph2 SiH(OEt). Both stoichiometric and catalytic reactions using 1a lead to the recovery of [AuCl(PCy3 )] from the reaction mixture. Graphical abstract: Image 1 Highlights: New gold complexes with chlorosilyl and chlorogermyl ligands characterized fully. Reaction pathway determined by results of kinetic study and isotope-labeling study. Stoichiometric reaction of water and ethanol with the complexes to afford silanol and silyl ether. Catalytic Si–O bond-forming reactions promoted by the Au complex that keeps Cl atom during the reaction.